Cytotoxic and bacteriocidal activities of psychotria rostrata - Mahmud, Zurinah; Musa, Mustaffa; Ismail, Norhayati; Lajis, Nordin H. (Informa Healthcare, 1993)
Quadrigemine B, a major alkaloid of Psychotria rostrata, was shown to be cytotoxic with HEp-2 cells and normal human lymphocytes. The cytotoxicity was time- and dose-dependent. Bacteriocidal activity was also shown by this compound toward Escherichia coli and Staphylococcus aureus.